2011
DOI: 10.1088/0022-3727/44/37/372001
|View full text |Cite
|
Sign up to set email alerts
|

A key inactivation factor of HeLa cell viability by a plasma flow

Abstract: Recently, a plasma flow has been applied to medical treatment using effects of various kinds of stimuli such as chemical species, charged particles, heat, light, shock wave and electric fields. Among them, the chemical species are known to cause an inactivation of cell viability. However, the mechanisms and key factors of this event are not yet clear. In this study, we focused on the effect of H2O2 in plasma-treated culture medium because it is generated in the culture medium and it is also chemically stable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 22 publications
4
64
0
1
Order By: Relevance
“…Our results support this and other hypotheses that attributed the cytotoxic effects of plasma to apoptosis resulting from ROS uptake into tumor cells [14,26]. Only SC-2-NU cells showed an inverse result.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results support this and other hypotheses that attributed the cytotoxic effects of plasma to apoptosis resulting from ROS uptake into tumor cells [14,26]. Only SC-2-NU cells showed an inverse result.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, several therapeutic trials have been completed in the fields of tissue sterilization, blood coagulation, wound-healing promotion, and dental bleaching [11][12][13]. Additionally, it has been reported that plasma can exert antiproliferative effects on various cancer cell lines, possibly through induction of apoptosis [6,14,15]. Ultimately, it could develop into a treatment option alongside conventional cytotoxic agents or radiotherapy in the field of oncology [6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to elucidate the interference mechanism between the plasma flow and cells, analysis of the cellular response at the level of gene expression is important. In the present study, we assessed the response of HeLa cells to a culture medium exposed to plasma for 40 s, a much shorter time than in the previous study [18]. Different from our previous study [18], this irradiation level allows the cells to survive without apparent induction of necrosis.…”
Section: Introductionmentioning
confidence: 93%
“…In the present study, we assessed the response of HeLa cells to a culture medium exposed to plasma for 40 s, a much shorter time than in the previous study [18]. Different from our previous study [18], this irradiation level allows the cells to survive without apparent induction of necrosis. The gene expression of HeLa cells was broadly analyzed by a DNA microarray in plasmatreated medium and H 2 O 2 -added medium as compared with expression in a regular culture medium.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation